Laugier–Hunziker syndrome: A rare cause of diffuse orofacial pigmentation - Ashwini Deshpande; Silky R Punyani (Medical Journal of Dr. D.Y. Patil Vidyapeeth, 2020)
Laugier–Hunziker syndrome (LHS) is lesser known and important differential of the multifocal mucocutaneous pigmentation. Essentially idiopathic in nature, this syndrome is characterized by multiple melanotic macules on the oral mucosa, lips, perioral region, and melanonychia. A young Indian male reported to us with a complaint of multiple brown-black spots on the lips and inner surface of the cheeks accompanied by the pigmentation of fingernail. The patient was evaluated for the possible causes of multifocal oral pigmentation. After taking an exhaustive clinical history and thorough investigations, no exact cause for this condition could be definitively ascertained. Eventually, he was diagnosed as a case of LHS, a rare cause of idiopathic oral pigmentation. The various differential diagnoses for the condition are also discussed.